Lung and Pleural Findings of Children with Pulmonary Vein Stenosis with and without Aspiration: MDCT Evaluation - Abbey J. Winant; Ryan Callahan; Sara O. Vargas; Kathy J. Jenkins; Vanessa Rameh; Patrick R. Johnston; Maria Niccum; Mirjam L. Keochakian; Edward Y. Lee (MDPI AG, 2022)
Purpose: To retrospectively compare the lung and pleural findings in children with pulmonary vein stenosis (PVS) with and without aspiration on multidetector computed tomography (MDCT). Materials and Methods: All consecutive children (≤18 years old) with PVS who underwent thoracic MDCT studies from August 2004 to December 2021 were categorized into two groups: children with PVS with aspiration (Group 1) and children with PVS without aspiration (Group 2). Two independent pediatric radiologists retrospectively evaluated thoracic MDCT studies for the presence of lung and pleural abnormalities as follows: (1) in the lung (ground-glass opacity (GGO), consolidation, nodule, mass, cyst(s), interlobular septal thickening, and fibrosis) and (2) in the pleura (thickening, effusion, and pneumothorax). Interobserver agreement between the two reviewers was evaluated by the proportion of agreement and the Kappa statistic. Results: The final study population consisted of 64 pediatric patients (36 males (56.3%) and 43 females (43.7%); mean age, 1.7 years; range, 1 day-17 years). Among these 64 patients, 19 patients (29.7%) comprised Group 1 and the remaining 45 patients (70.3%) comprised Group 2. In Group 1 (children with PVS with aspiration), the detected lung and pleural MDCT abnormalities were: GGO (17/19; 89.5%), pleural thickening (17/19; 89.5%), consolidation (16/19; 84.5%), and septal thickening (16/19; 84.5%). The lung and pleural MDCT abnormalities observed in Group 2 (children with PVS without aspiration) were: GGO (37/45; 82.2%), pleural thickening (37/45; 82.2%), septal thickening (36/45; 80%), consolidation (3/45; 6.7%), pleural effusion (1/45; 2.2%), pneumothorax (1/45; 2.2%), and cyst(s) (1/45; 2.2%). Consolidation was significantly more common in pediatric patients with both PVS and aspiration (Group 1) (p < 0.001). There was high interobserver agreement between the two independent reviewers for detecting lung and pleural abnormalities on thoracic MDCT studies (Kappa = 0.98; CI = 0.958, 0.992). Conclusion: Aspiration is common in pediatric patients with PVS who undergo MDCT and was present in nearly 30% of all children with PVS during our study period. Consolidation is not a typical radiologic finding of PVS in children without clinical evidence of aspiration. When consolidation is present on thoracic MDCT studies in pediatric patients with PVS, the additional diagnosis of concomitant aspiration should be considered.